Acceleration of a trailing positron bunch in a plasma wakefield accelerator. Issue 1 (December 2017) - Doche, A.; Beekman, C.; Corde, S.; Allen, J.; Clarke, C.; Frederico, J.; Gessner, S.; Green, S.; Hogan, M.; O'Shea, B.; Yakimenko, V.; An, W.; et al.
Abstract High gradients of energy gain and high energy efficiency are necessary parameters for compact, cost-efficient and high-energy particle colliders. Plasma Wakefield Accelerators (PWFA) offer both, making them attractive candidates for next-generation colliders. In these devices, a charge-density plasma wave is excited by an ultra-relativistic bunch of charged particles (the drive bunch). The energy in the wave can be extracted by a second bunch (the trailing bunch), as this bunch propagates in the wake of the drive bunch. While a trailing electron bunch was accelerated in a plasma with more than a gigaelectronvolt of energy gain, accelerating a trailing positron bunch in a plasma is much more challenging as the plasma response can be asymmetric for positrons and electrons. We report the demonstration of the energy gain by a distinct trailing positron bunch in a plasma wakefield accelerator, spanning nonlinear to quasi-linear regimes, and unveil the beam loading process underlying the accelerator energy efficiency. A positron bunch is used to drive the plasma wake in the experiment, though the quasi-linear wake structure could as easily be formed by an electron bunch or a laser driver. The results thus mark the first acceleration of a distinct positron bunch in plasma-based particle accelerators.